Formulasi Tablet Ekstrak Daun Kelengkeng (Euphoria Longana Lam) dengan Variasi Polivinil Pirolidone (PVP K-30) Sebagai Bahan Pengikat - Dwi Saryanti; Fatma Eka Saputri (Jurnal Kesehatan Farmasi, 2022)
Background: Longan leaf (Euphoria longana Lam) is one of the plants that can be used by the community as an antipyretic or fever reducer with phytochemical content of saponins, flavonoids, triterpenoids and steroids, tannins, and glycosides. The tablet preparation was chosen in the formulation because it has an accurate dosage per tablet or per unit of use. This study aims to determine the concentration of PVP K-30 can produce tablet preparations from longan leaf extract as a binder that has good physical stability.Methods: Longan leaf extract was obtained by extraction by maceration method using 96% ethanol as solvent. Tablet preparations were made with ethanol extract of longan leaves with varying concentrations of PVP K-30 2%,3%, and 4%. The granule physical stability test includes: water content test, angle of repose test, flow time test, and determination test. The results of the physical stability test of the granules all met the requirements. The tablet physical stability test was carried out on days 0, 7, 14, 21 including: organoleptic test (shape, color, smell, and taste), weight uniformity test, size uniformity test, hardness test, friability test and disintegration time test. Results: The best concentration of PVP K-30 as a binder in longan leaf extract tablets (Euphoria longana Lam) was formula I with a concentration of 2% PVP K-30 binder with a weight uniformity test value (1.611±0.056) size uniformity test ( 1.036±0.046) friability test (0.545±0.090) hardness test (5.494±0.080) disintegration time test (10:22±0.055). Conclusion: Higher levels of PVP K-30 increase hardness, reduce friability and increase tablet disintegration time